Comparative Evaluation of Oxidative Stress in Type-2 Diabetes Mellitus in Relation to Controlled Vs Uncontrolled Diabetes - Beg, Aisha; Thakur, Rajesh Kumar; Saxena, Rahul; Rai, Gladys; Srivastava, Saurabh; Gambhir, Jasvinder Kaur (Annals of Pathology and Laboratory Medicine, 2019)
Background: Type 2 Diabetes Mellitus (T2DM) is associated with the production of excess free radicals which are not neutralised by available antioxidants thereby, leading to oxidative stress (OS). The extent of oxidative damage and resulting diabetic complications may be determined by the degree of hyperglycemia viz; controlled vs uncontrolled T2DM. Aim: To evaluate and compare oxidative stress in T2DM patients with good glycemic control vs uncontrolled T2DM, by estimating malondialdehyde (MDA, index of lipid peroxidation), ferric acid reducing ability of plasma (FRAP as total antioxidant capacity, TAC). Methods: The study included 50 healthy controls (Gp I) and 100 T2DM patients which were further divided into: Gp II having good glycemic control (HbA1c â‰¤ 7.0%) and Gp III with uncontrolled T2DM (HbA1c >7.0%)(n=50 each). Fasting & post-prandial plasma glucose, HbA1c, MDA, FRAP & hsCRP were estimated using standard methods. Result: MDA was significantly higher and FRAP was significantly lower in T2DM patients as compared to healthy controls. Further, T2DM patients (Gp III) with uncontrolled hyperglycemia had higher degree of oxidative stress vs Gp II patients with good glycemic control. Moreover there was: i) A significant positive correlation between HbA1c & MDA (p<0.001),& ii) Significant negative correlation between HbA1c & FRAP and MDA & FRAP (p<0.001) in T2DM patients. Conclusion: Oxidative stress in T2DM patients is directly proportional to the degree of hyperglycemia measured as HbA1c.Therefore it is important to maintain tight glycemic control in T2DM patients (HbA1c â‰¤ 7%), to decrease oxidative stress and thereby delay the onset of diabetic complications.